The role of Lokki village officials in improving infrastructure development in Lokki village, Huamual sub-district, West Seram Regency. - Geral Matulessy; Andreas M.D Ratuanak; Jurgen R. Litualy (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
This research aims to determine the extent of the role of Negeri Lokki officials in enhancing infrastructure development in Lokki Village, Huamual District, West Seram Regency. This study employs a socio-legal research method with a qualitative approach. Data was collected through observation and in-depth interviews with officials, the Village Consultative Body (BPD), and several community leaders in Negeri Lokki. The findings indicate that infrastructure development in Negeri Lokki has been quite significant for the community. However, there is still a lack of coordination between the Village Government and the Regional Government regarding recurring issues in the village, particularly land disputes and funding shortages. Consequently, the Village Government faces difficulties in implementing programs provided by the Regional or Central Government.